Description of the characteristics influencing the therapeutic management of infertile couples in western Algeria - Belhachemi N; Zelmat SA; Chafi B; Foughal M; Mohand Arabe W (Global Journal of Fertility and Research - Peertechz Publications, 2020)
Objective: The aim of this work is to describe and identify the characteristics that can influence the care of these infertile couples. Material and method: This is a prospective, monocentric study, extending over a period of four years. It is descriptive of a sample of 760 infertile couples treated in the gynaecology and obstetrics department of the Oran hospital and university establishment of 1st November 1954.  Results: The study revealed that primary infertility was 74%. The average duration of infertility was 4.8 ± 0.2 years (minimum 6 months, maximum 25 years); the average age of infertile couples was 33.2 ± 0.4 years (minimum 18 years, maximum 45 years) in women and 39.5 ± 0.5 years (minimum 23 years, maximum 71 years) in men. The male origin of infertility was 30.4%, mixed at 29.2%, female at 27% and unexplained at 13.4%. Oligo-astheno-severe teratospermia dominated male infertility at 30.4%. Tubal causes 23.4% and ovulatory causes 22.8% were mainly of female origin of infertility.  Conclusion: The study of these characteristics showed a delay in the treatment of infertile couples. The primary type and long duration of infertility and the advanced age of both women and men make the chances of conception minimal. The male origin of infertility is more important than the female origin, suggesting a deterioration in sperm parameters. Tubal causes in the female origin of infertility are important because of the increasing prevalence of sexually transmitted infections.